Unusual gastric mucosal infiltration by a medullary thyroid carcinoma: a case report. (December 2016) - Karrasch, T.; Doppl, W.; Roller, F.; Schäffler, A.; Schäffer, R.; Gattenlöhner, S.
Abstract Background Medullary thyroid carcinoma accounts for approximately 1 to 2 % of all thyroid carcinoma cases. The most common route of dissemination is to locoregional lymph nodes. Distant metastases commonly affect bones, lungs, and liver. We present a case of a white woman with a 25-year history of medullary thyroid carcinoma on multiple medications including tyrosine kinase inhibitor therapy for the last 11 months, who exhibited unusual diffuse infiltration of advanced stage medullary thyroid carcinoma to her gastric mucosa. Case presentation A 53-year-old white woman presented with increasing fatigue, loss of appetite, and severe epigastric pain radiating to her back. She had a history of medullary thyroid carcinoma (pT2pN1b), diagnosed 25 years ago and treated by complete thyroidectomy and repeated bilateral cervical lymph node dissection. Medical therapy included octreotide 20 mg every 4 weeks, which was switched to the tyrosine kinase inhibitor vandetanib 300 mg/day 11 months ago when computed tomography scanning revealed progressive mediastinal lymph node and diffuse and symptomatic pulmonary metastases. Of note, she demonstrated macroscopically stable pulmonary and mediastinal lymph node metastases; however, her calcitonin serum levels dramatically increased. Computed tomography scanning revealed a single new intrahepatic lesion (4 mm) as well as multiple (>10) new supraclavicular lesions suggestive of medullary thyroid carcinoma progress. As proven by gastric biopsy and immunohistochemical evaluation, her epigastric pain was explained by a diffuse infiltration of her gastric mucosa by metastatic medullary thyroid carcinoma. Subsequently, she rapidly deteriorated and died. Conclusions The current case report shows for the first time an unusual metastatic infiltration of the gastric mucosa by medullary thyroid carcinoma. When treating these patients, it is important to include this differential diagnosis during follow-up.